Can Information Heterogeneity Explain the Exchange Rate Determination Puzzle? - Philippe Bacchetta; Eric van Wincoop (Swiss National Bank, Study Center Gerzensee, 2003)
Empirical evidence shows that observed macroeconomic fundamentals have little explanatory power for nominal exchange rates (the exchange rate determination puzzle). On the other hand, the recent "microstructure approach to exchange rates" has shown that most exchange rate volatility at short to medium horizons is related to order flow. In this paper we introduce symmetric information dispersion about future fundamentals in a dynamic rational expectations model in order to explain these stylized facts. Consistent with the evidence the model implies that (i) observed fundamentals account for little of exchange rate volatility in the short to medium run, (ii) over long horizons the exchange rate is closely related to observed fundamentals, (iii) exchange rate changes are a weak predictor of future fundamentals, and (iv) the exchange rate is closely related to order flow over both short and long horizons.
Keywords: 330; Monetäre Wechselkurstheorie; Anlageverhalten; Informationsökonomik; Theorie